Applying the Sashiko Technique to Classic Elegant Womenswear Inspired by Gedong Songo Temple - Afidatun Nisa'; Noor Laila Ramadhani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study aimed to develop an innovative fashion design by integrating the cultural heritage of Semarang Regency, Indonesia, with a traditional Japanese decorative technique. Specifically, the study explored the application of the sashiko technique to classic elegant womenswear inspired by Gedong Songo Temple. The research employed a Research and Development (R&D) method to design, produce, and evaluate the clothing product. The findings showed that the application of the sashiko technique resulted in a distinctive and visually appealing fashion product. The garment was designed as a convertible outfit that can be styled in three different looks, which enhances its aesthetic and functional value. Its main uniqueness lies in the harmonious cultural contrast created through the integration of local Indonesian heritage and Japanese textile ornamentation. The architectural elements of Gedong Songo Temple were successfully transformed into dynamic textile motifs through the use of the hitomezashi sashiko pattern. Expert validation indicated that the product achieved an average score of above 4.0, which categorized it as highly feasible for use. The study concludes that the sashiko technique functions not only as a decorative element but also as a means of enhancing the aesthetic value, exclusivity, and cultural significance of fashion products rooted in local wisdom. This design may also serve as a source of inspiration for future fashion innovation.